The world of labour. A discussion of the present and future of trade unionism. With a frontispiece by W. Dyson (Bell, 1919)
With bibliogr. and index. Facsimile reprint: [Brighton], Harvester Press, 1973. Ed. with and introd. and notes by J. Lovell. 39 p. (Society and the Victorians. General ed.: J. Spiers, 11).